Contrast medium‐induced transient severe leukopenia. Issue 2 (25th October 2017) - Hongo, Takashi; Nozaki, Satoshi; Tsuchiya, Midori; Inaba, Mototaka; Takahashi, Kenji; Fujiwara, Toshifumi
Abstract : Case: Contrast medium‐induced transient leukopenia is very rare. Here, we report a case of a 73‐year‐old man diagnosed with contrast media‐induced transient leukopenia. The patient underwent abdominal contrast‐enhanced computed tomography, where he was given non‐ionic iodinated contrast medium i.v. His medical history included an allergic reaction to a different contrast medium. One hour later, the patient was admitted to the emergency department complaining of chest discomfort. He had leukopenia and a fever (temperature of 38.9°C). Complete blood count showed a white blood cell count of 930/μL and an absolute neutrophilic count of 232/μL. Outcome: The patient was given i.v. antibiotics and 5 mg chlorpheniramine maleic acid, 20 mg famotidine, and 125 mg methylprednisolone. The patient's white blood cell count recovered the next day, and he was discharged after 2 days of hospitalization. Conclusion: We diagnosed the patient with contrast media‐induced transient leukopenia, which is a rare phenomenon. Abstract : Our article reports a rare case of a patient that developed transient agranulocytosis after receiving a contrast medium for abdominal contrast‐enhanced computed tomography. We diagnosed the patient with idiosyncratic agranulocytosis that was induced by the contrast medium, which is a rare phenomenon.